hubungan Correlation between Knowledge and Attiude of Mother with Giving Vitamin A to Toddlers: Hubungan pengetahuan dan sikap ibu dengan pemberian vitamin A pada anak balita di puskesmas pariaman kota pariaman tahun 2017 - Prasetyaningsih Prasetyaningsih (Jurnal Kesehatan Komunitas, 2019)
Background: Vitamin A is one of the important nutrients that are fat-soluble and stored in the liver, cannot be made by the body, so it must be fulfilled from the outside (essential). 40 million children suffer from vitamin A deficiency and 13 million children show clinical symptoms of eye disorders. Pariaman Health Center is the region with the lowest coverage of vitamin A, which is 74% of 1546 toddlers. The purpose of this study was to determine the correlation between the level of knowledge and attitudes of mothers with giving vitamin A for toddler in Pariaman Health Center, pariaman city, 2017. Methods: This type of analytic descriptive research using the approach is cross sectional. The study was conducted in Pariaman Health Center in September 2017. The study population was mothers who had toddler who were in the work area of Pariaman Health Center totaling 1,546 people, 93 samples were obtained using accidental sampling method Data processing was Univariate and Bivariate using Chi Square analysis computerized. Results: Univariate results showed that 51.6% had low knowledge, 64.5% had a negative attitude, 64.5% gave vitamin A capsules for toddlers. There is a significant relationship between the knowledge of mothers with giving vitamin A for toddlers, p value 0.001 <0.05. There was a significant correlation between the attitudes of mothers with giving vitamin A, p value 0.001 <0.05. Conclusion: The low coverage of vitamin A in Pariaman Health Center was apparently influenced by a lack of knowledge and also a negative mother's attitude. It is expected that the health center will further improve health services to the community, should counseling about vitamin A be held every month so that mothers' understanding of vitamin A increases